Human development report 2007/2008 : fighting climate change : human solidarity in a divided world - United Nations Development Programme; Palgrave Connect Online service (New York: United Nations Development Programme: Palgrave Macmillan, 2007)
Human development is about putting people at the centre of development. It is about people realizing their potential, increasing choice and enjoying the freedom to lead the lives they value. Created in 1990, the Human Development Report has explored themes including gender equity, democracy, human rights, globalization, cultural liberty and water scarcity. Climate change is the greatest challenge facing humanity at the start of the 21st Century. Failure to meet that challenge raises the spectre of unprecedented reversals in human development. The world's poorest countries and poorest people will bear the brunt. The past years have witnessed the emergence of a growing consensus on climate change. Governments across the world have seen the warning signs. The science linking global warming to human activity is unequivocal. The economic case for action is compelling: the costs of inaction will heavily outweigh the costs of action. Yet the politics lags behind the science and the economics. Collectively, the world's governments are failing to act with the urgency demanded by the scale of the threat. The window of opportunity for avoiding dangerous climate change is closing fast. This year's Human Development Report explains why we have less than a decade to change course and start living within our global carbon budget. It explains how climate change will create long-run low human development traps, pushing vulnerable people into a downward spiral of deprivation. Because climate change is a global problem with global causes and effects, it demands a global response with countries acting on the basis of their historic responsibility and capabilities. The Human Development Report 2007 will be launched in November.
Fighting climate change: human solidarity in a divided world -- The 21st Century climate challenge -- Climate shocks: risk and vulnerabililty in an unequal world -- Avoiding dangerous climate change: strategies for mitigation -- Adapting to the inevitable: national action and international cooperation.
Includes bibliographical references and index.
Keywords: United Nations Development Programme; United Nations Development Programme; Climatic changes -- -- Economic aspects; Global warming -- -- Economic aspects; Greenhouse gas mitigation; Global warming; SOCIAL SCIENCE -- -- Human Geography; Climatic changes -- -- Environmental aspects; Electronic books